2009
DOI: 10.3310/hta13580
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral drugs for the treatment of influenza: a systematic review and economic evaluation

Abstract: How to obtain copies of this and other HTA programme reports An electronic version of this publication, in Adobe Acrobat format, is available for downloading free of charge for personal use from the HTA website (www.hta.ac.uk). A fully searchable CD-ROM is also available (see below).Printed copies of HTA monographs cost £20 each (post and packing free in the UK) to both public and private sector purchasers from our Despatch Agents.Non-UK purchasers will have to pay a small fee for post and packing. For Europea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
0
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(95 citation statements)
references
References 9 publications
2
91
0
2
Order By: Relevance
“…Two recent systematic reviews, based on evidence from prophylaxis (four trials), treatment (12 trials), and post-exposure prophylaxis (four trials), both concluded that these drugs did not result in meaningful symptomatic improvement in seasonal influenza. 119,120 Whether oseltamivir reduces influenza-related LRTI complications remains unclear. The 2005 Cochrane systematic review concluded that it did.…”
Section: Prevention and Treatment Of Seasonal Influenzamentioning
confidence: 99%
“…Two recent systematic reviews, based on evidence from prophylaxis (four trials), treatment (12 trials), and post-exposure prophylaxis (four trials), both concluded that these drugs did not result in meaningful symptomatic improvement in seasonal influenza. 119,120 Whether oseltamivir reduces influenza-related LRTI complications remains unclear. The 2005 Cochrane systematic review concluded that it did.…”
Section: Prevention and Treatment Of Seasonal Influenzamentioning
confidence: 99%
“…This is partly due to the publication of the method guides by NICE (22,23) which promotes the use of relevant methods but also due to the development of freely available, more user-friendly, Bayesian specialist software packages such as WinBUGS (10) (24) presented separate meta-analyses for the 2 active treatments (zanamivir and oseltamivir) under review compared to placebo as no head-to-head trials of the 2 active treatments existed. However, the updated review, published in 2009 (25), applied explicit Bayesian methods to obtain an indirect estimate of the 2 treatments compared to one another as well as placebo. Similarly, the recently published review of obesity treatments(26) collated and updated the previous 2 HTAs (evaluating the effectiveness and cost-effectiveness of Orlistat (27) and Sibutramine (28) separately) using explicit Bayesian mixed treatment comparison methods to bring the evidence together within a single analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent systematic reviews and meta-analyses of the therapeutic use of NIs, 70,216,217 show that a clinically beneficial effect of oseltamivir and zanamivir (Relenza ® , GSK) depends on treatment starting within 48 hours of first symptoms when seasonal (inter-pandemic) influenza is circulating. In our study, only the Quidel QuickVUE Influenza A&B test provided results soon enough to influence treatment decisions that might benefit patients -and then only to a small percentage (150/1240, 12.1%) of admissions.…”
Section: Methods For the Diagnosis Of Respiratory Infectionsmentioning
confidence: 99%